Ethics and Moral Education Based on Seyyed Hussein Nasr View - Lak, Ahmad; Beheshti, Saeed; Kazem Akrami, Seyyed; Imani, Mohsen (International Journal of Psychosocial Rehabilitation, 2020)
Background: The purpose of this study is to explain the views of Seyyed Hussein Nasr on the foundations of ethics and principles of moral education. Nasr is one of the prominent thinkers who see ethics and moral education as a process developed from the inner. He discusses the characteristics of a person as determinants of the normalization of behavior. In the realm of morality, he is more concerned with Aristotle's contemplative virtue ethics. Methods: The study is a Qualitative one, and conceptual analysis and inference method have used to achieve the results. Results: According to Nasr's view, ethics is the way to perfection of the human soul from the imperfect stages of the soul to the full steps of it. Nasr's intellectual framework is traditionalism and wisdom. The foundations of ethics described in three ontological, epistemological and anthropological domains and the main principles of his moral education include developing a moral conscience, Love of kindness and friendship, Strengthen the spirit of truth-seeking. Conclusions: By applying the principles outlined in Nasr's perspective, teachers and educators can enhance students' accountability and proper recognition of daily moral judgments. Given that Nasr has emphasized the principles of moral education on the tension between religious and moral education, it suggested that other scholars consider religious education, especially religious ethics, from his point of view.